Artificial Intelligence in Religious Education: A Comparative Ethical-Pedagogical Framework for Islam and Christianity in Nigeria - Moses Adeolu AGOI; Bukola Abosede FOLARANMI; Oluwakemi Racheal OSHINOWO; Asep Suraya Maulana; Hendri Hermawan Adinugraha (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This research examines the application of artificial intelligence (AI) as an innovative approach in Religious Education (RE), with a comparative focus on Christian and Islamic educational contexts. It aims to explore the potential benefits, challenges, and ethical implications of integrating AI into faith-based learning. The study employs a qualitative literature review by analyzing recent research findings and empirical studies related to AI use in religious education. Data were drawn from scholarly articles, case studies, and educational reports addressing AI tools such as chatbots, adaptive learning systems, virtual assistants, and curriculum analytics in both Christian and Islamic settings. The findings indicate that AI can enhance religious learning by supporting personalized instruction, increasing access to educational resources, and promoting interactive learning experiences. In Islamic Religious Education, AI applications have been effective in improving accessibility and contextual understanding while emphasizing the need to align technology with religious values. Similarly, AI innovations in Christian education—such as adaptive scripture delivery and digital text analysis—have shown promise in engaging digital-age learners. However, ethical and theological concerns remain, including risks of technological dependence, data security issues, and potential weakening of spiritual relationships. This study concludes that responsible, value-oriented AI integration is essential to preserve doctrinal integrity while improving educational outcomes. Future research should focus on ethical AI governance, comparative religious education models, and large-scale evaluations of learning effectiveness [Penelitian ini mengkaji penerapan kecerdasan buatan (AI) sebagai pendekatan inovatif dalam Pendidikan Agama (RE), dengan fokus perbandingan pada konteks pendidikan Kristen dan Islam. Tujuannya adalah untuk mengeksplorasi potensi manfaat, tantangan, dan implikasi etis dari integrasi AI dalam pembelajaran berbasis agama. Studi ini menggunakan tinjauan literatur kualitatif dengan menganalisis temuan penelitian terbaru dan studi empiris terkait penggunaan AI dalam pendidikan agama. Data diperoleh dari artikel ilmiah, studi kasus, dan laporan pendidikan yang membahas alat AI seperti chatbot, sistem pembelajaran adaptif, asisten virtual, dan analisis kurikulum di lingkungan Kristen dan Islam. Temuan menunjukkan bahwa AI dapat meningkatkan pembelajaran agama dengan mendukung instruksi yang dipersonalisasi, meningkatkan akses ke sumber daya pendidikan, dan mempromosikan pengalaman pembelajaran interaktif. Dalam Pendidikan Agama Islam, aplikasi AI telah efektif dalam meningkatkan aksesibilitas dan pemahaman kontekstual sambil menekankan pentingnya menyelaraskan teknologi dengan nilai-nilai agama. Demikian pula, inovasi AI dalam pendidikan Kristen—seperti pengiriman teks suci yang adaptif dan analisis teks digital—telah menunjukkan potensi dalam melibatkan pembelajar di era digital. Namun, kekhawatiran etis dan teologis tetap ada, termasuk risiko ketergantungan teknologi, masalah keamanan data, dan potensi melemahnya hubungan spiritual. Studi ini menyimpulkan bahwa integrasi kecerdasan buatan (AI) yang bertanggung jawab dan berorientasi nilai sangat penting untuk menjaga integritas doktrinal sambil meningkatkan hasil pendidikan. Penelitian di masa depan sebaiknya fokus pada tata kelola AI yang etis, model pendidikan agama yang komparatif, dan evaluasi skala besar mengenai efektivitas pembelajaran.]